2021
DOI: 10.3389/fimmu.2021.597951
|View full text |Cite
|
Sign up to set email alerts
|

Breaching the Bacterial Envelope: The Pivotal Role of Perforin-2 (MPEG1) Within Phagocytes

Abstract: The membrane attack complex (MAC) of the complement system and Perforin-1 are well characterized innate immune effectors. MAC is composed of C9 and other complement proteins that target the envelope of gram-negative bacteria. Perforin-1 is deployed when killer lymphocytes degranulate to destroy virally infected or cancerous cells. These molecules polymerize with MAC-perforin/cholesterol-dependent cytolysin (MACPF/CDC) domains of each monomer deploying amphipathic β-strands to form pores through target lipid bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 106 publications
(239 reference statements)
0
11
0
Order By: Relevance
“…The microbial host-protein interaction map indicated that HSP90 was associated with the host protein, Q3MHN2, which participates in the immune system process and responds to stimuli affecting the host. Q3MHN2 contains a membrane attack complex (MAC)/perforin domain, and the MAC of the complement system is a well-characterized innate immune effector (Merselis et al, 2021). These findings proved that the relationship between neonatal calves infected by E. coli K99 and Batrachochytrium salamandrivorans may be at the strain level instead of at the species level, and that its sub-species level dysbiosis may be related to differences between immune functions in response to oxidative stress.…”
Section: Host-protein In Jejunum Of Neonatal Calvesmentioning
confidence: 81%
“…The microbial host-protein interaction map indicated that HSP90 was associated with the host protein, Q3MHN2, which participates in the immune system process and responds to stimuli affecting the host. Q3MHN2 contains a membrane attack complex (MAC)/perforin domain, and the MAC of the complement system is a well-characterized innate immune effector (Merselis et al, 2021). These findings proved that the relationship between neonatal calves infected by E. coli K99 and Batrachochytrium salamandrivorans may be at the strain level instead of at the species level, and that its sub-species level dysbiosis may be related to differences between immune functions in response to oxidative stress.…”
Section: Host-protein In Jejunum Of Neonatal Calvesmentioning
confidence: 81%
“…Rho GDIα retains CDC42, RAC1, and RHOA in inactive cytosolic pool and keeps it from degradation ( 43 ). MPEG1 (macrophage expressed gene 1) inhibits the acidification of phagocytic vacuole ( 44 ). Blockade of CD74 receptor or its ligand macrophage migration inhibitory factor (MIF) reduces cell invagination ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“… 63 The terminal membrane attack complex (MAC) complement components C5b, C6, and C7–9 of mammals also all share a MACPf fold with perforin. However, none of the complement components or the distantly related bacteriocidal macrophage protein perforin-2 64 have a C2 domain. Other more distant human pore-forming proteins such as gasdermin D 65 and antimicrobial toxin granulysin 66 have no structural similarity to perforin and are not blocked by perforin inhibitors.…”
Section: Small Molecule Inhibitors Of Perforinmentioning
confidence: 99%